HOW THE RUSSIA-UKRAINE WAR CHANGED THE MODERN WORLD - Chitadze, Nika (Стратегічна панорама, 2023)
The author analyzes the geopolitical, economic, energy, military, historical, informational, and other important factors, which played a role in the Russian military aggression against Ukraine. Particularly, the author presents a comprehensive overview of the reasons behind the implementation of the intervention in Ukraine and the violation of the main principles of morality and international law by Russia. Furthermore, the author shows how Russia is losing geopolitical influence in the world and particularly in the post-soviet space, which the Kremlin considers as a zone of geopolitical and geostrategic interests of Russia after the disintegration of the Soviet Union. The author also examines the economic consequences of the war, including how the military operation has damaged the Russian economy, and how this has negatively affected the Russian government’s budget. One of the results of it is the decreasing volume of Russian oil and gas exports, especially in the European market. In this context, some aspects of how the war affects the global economy are also discussed and analyzed. Regarding military aspects, the statistical data related to Russian losses in the war, including military personnel and military techniques also are considered in the framework of the research. In the research, attention is paid to the importance of analyzing some historic factors, related to the imperialistic policy of the Russian empire, the Soviet Union, and the Russian Federation accordingly from the 19th century till now. Particularly, the focus is on kinds of violations that have been implemented by their rulers against different states and nations, including mass deportations and genocides of the civilian population. In conclusion, the author presents possible scenarios for developments related to the Russia-Ukraine war.